n Ondersoek na voetafwykings en voethoudings by blinde seuns - Van der Merwe, C. A.(Carel Andries),1920- (Stellenbosch : Stellenbosch University, 2012)
Verhandeling (B. Ed. Ph.) -- Universiteit van Stellenbosch, 1944.